Modified resin coated double-doped microcrystalline graphite negative electrode material as well as preparation method and application thereof

By activating microcrystalline graphite and double doping of metal salts and sulfur, and coating nitrogen-doped hard carbon material to form a negative electrode material with a core-shell structure, the sodium ion is solved during the charging and discharging of sodium ion battery negative electrode material. The serious loss problem significantly improves the stability and electrochemical properties of the material.

CN119481010APending Publication Date: 2025-02-18SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD

Patent Information

Application Number
CN202411702815.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials have severe loss of sodium ions during charging and discharging, resulting in insufficient sodium storage capacity and cycle stability.

Method used

The microcrystalline graphite is activated to form a porous structure and double-doped metal salt and sulfur to form a three-dimensional mesh porous structure. The surface is then coated with nitrogen-doped hard carbon material to form a core-shell structure to improve the conductivity and structural stability of the material.

Benefits of technology

It significantly reduces the loss of sodium ions during charging and discharging, improves the stability and electrochemical performance of the material, and enhances the rate cycling performance and cycle stability of the sodium ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481010A_ABST
    Figure CN119481010A_ABST
Patent Text Reader

Abstract

The invention discloses a modified resin coated double-doped microcrystalline graphite negative electrode material as well as a preparation method and application thereof. The modified resin coated double-doped microcrystalline graphite negative electrode material has a core-shell structure, wherein an inner core is a three-dimensional network porous structure formed by metal salt and sulfur double-doped microcrystalline graphite; metal salt in the inner core forms a chemical bond between sulfur and microcrystalline graphite to provide a bridge for bonding of microcrystalline graphite and sodium; the shell is a coating layer formed by coating the surface of the inner core with modified resin and carbonizing the modified resin, and has a three-dimensional porous conductive network structure. According to the invention, through the activation process, increase of interlamellar spacing and active sites of microcrystalline graphite, and double doping of sulfur element and metal salt, the doping amount of sulfur and metal salt in microcrystalline graphite is improved, meanwhile, the metal salt forms chemical bonds between sulfur and microcrystalline graphite, sodium ion loss in the charge and discharge process is reduced, and the material stability is improved; and the rate cycle performance of the sodium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a modified resin-coated dual-doped microcrystalline graphite negative electrode material, a preparation method thereof, and applications thereof. Background Art

[0002] With the progress and development of society, the consumption of non-renewable resources such as oil, coal, and natural gas is increasing. How to reduce the use of such non-renewable energy and find a substitute has become one of the important research directions. Electrochemical energy storage elements represented by lithium-ion batteries are highly favored because of their high energy density, green and clean, long cycle life and other advantages. However, lithium-ion batteries cannot meet the growing market demand due to their tight lithium resources, difficult development and uneven distribution, which also limits the large-scale application of lithium-ion batteries. Therefore, sodium-ion batteries came into being. Sodium-ion batteries are regarded as possible next-generation secondary batteries because of the wide distribution of sodium resources, low raw material prices, and the same main group characteristics as lithium.

[0003] The main components of sodium ion batteries are generally divided into negative electrode materials, positive electrode materials, separators, electrolytes and shells, among which the negative electrode materials, as an important component, play a decisive role in the performance of sodium ion batteries. However, the radius of sodium ions (0.97nm) is larger than that of lithium ions (0.68nm), making it difficult for sodium ions to be effectively deintercalated in graphite materials. Sodium ions also require more energy when intercalated between graphite layers, and graphite is difficult to form stable graphite sodium intercalation compounds with sodium, so graphite materials are not suitable for sodium storage. In order to solve the above technical problems, new negative electrode materials are studied and developed to realize the intercalation and deintercalation of sodium ions to improve the electrochemical properties of sodium ion batteries, and graphite modification, coating, doping, oxidation expansion and other methods are one of the methods to improve the electrochemical properties of negative electrode materials.

[0004] On the other hand, natural microcrystalline graphite can be used as the negative electrode material of sodium ion batteries because of its good conductivity, large reserves and isotropy. However, on the one hand, the crystal diameter of microcrystalline graphite is usually less than 1 μm, and it is in the form of a microcrystalline aggregate, because its grains are small and the particle layer structure is unevenly oriented to form a chaotic layer structure; on the other hand, although microcrystalline graphite has an isotropic property and a single-direction expansion of about 3%, it is not easy to cause structural damage, but the mechanical strength of microcrystalline graphite is low and it is very easy to pulverize. Therefore, the prior art usually requires modification when using it as a negative electrode material. For example, Chinese invention patent CN107437613A provides a method for preparing a microcrystalline graphite-hard carbon composite negative electrode material, using natural microcrystalline graphite and biomass raw materials as initial raw materials, preparing a biomass hard carbon negative electrode material by a low-temperature pre-fixation and high-temperature carbonization method, and then composite granulating with microcrystalline graphite to obtain a battery negative electrode material; the invention improves the mechanical properties of microcrystalline graphite by compounding microcrystalline graphite with hard carbon, thereby improving the capacity and rate performance of the negative electrode material. For another example, Chinese invention patent CN109616639A discloses a hard carbon-coated expanded microcrystalline graphite material, its preparation method and application in sodium ion batteries. After the microcrystalline graphite is ball-milled, it is subjected to chemical intercalation treatment and expansion treatment to obtain expanded microcrystalline graphite; the expanded microcrystalline graphite is coated with a resin carbon source and then carbonized. The composite material has good conductivity, high sodium storage capacity and stable structure. It is used as a negative electrode material for preparing sodium ion batteries, showing high specific capacity, good rate performance and long cycle stability. Obviously, the negative electrode material obtained by hard carbon-coated microcrystalline graphite composite has been widely used in sodium ion batteries; however, in actual applications, the negative electrode material of the sodium ion battery obtained by using the microcrystalline graphite modified by the above method as the matrix material has only improved its sodium storage capacity and product cycle stability, and the loss of sodium ions during the charge and discharge process is still very serious. The reason is that, on the one hand, due to the special morphology of microcrystalline aggregates and small grains, especially the lamellar structure of the grains forms a chaotic layer structure due to different orientations, so that even after chemical intercalation or expansion treatment, it is impossible to achieve a significantly improved technical effect; on the other hand, since microcrystalline graphite and sodium cannot form stable graphite-intercalated sodium compounds, the negative electrode material has poor sodium storage and the loss of sodium ions during the charge and discharge process is very serious, resulting in poor cycle stability of the negative electrode material. Summary of the invention

[0005] In order to solve the above-mentioned technical problems, the present invention provides a modified resin-coated sulfur-doped microcrystalline graphite negative electrode material, a preparation method thereof, and an application thereof.

[0006] In order to achieve the above-mentioned object, the present invention provides a modified resin-coated dual-doped microcrystalline graphite negative electrode material, which has a core-shell structure, including an inner core and an outer shell; the inner core is a three-dimensional mesh porous structure formed by microcrystalline graphite dual-doped with metal salt and sulfur; the metal salt in the inner core forms a chemical bond between sulfur and microcrystalline graphite, providing a bridge for the bonding of microcrystalline graphite and sodium; the outer shell is a coating layer formed by carbonization of a modified resin coated on the surface of the inner core, having a three-dimensional porous conductive network structure. Metal doping can form defects such as sodium ion vacancies inside the material, improve the material's electrical conductivity, and enhance the sodium storage capacity. Secondly, metal doping can form ion transmission channels, accelerate the sodium ion transmission rate, and improve the electrochemical performance of the material.

[0007] Preferably, in the shell, the modified resin is a nitrogen-doped organic resin material; the organic resin material includes a combination of one or more of epoxy resin, phenolic resin, petroleum resin, urea-formaldehyde resin, and furan resin.

[0008] Preferably, the nitrogen source in the nitrogen doping is one or more combinations of melamine, polypropylamine, polyvinyl pyrrolidone, ammonium chloride and dopamine.

[0009] Preferably, in the inner core, the metal salt may be a combination of one or more of nickel sulfate, sodium carbonate, manganese sulfate, cobalt nitrate and ferric chloride.

[0010] Preferably, the sulfur doping is at least one of sublimated sulfur, sodium thiosulfate, and carbon disulfide.

[0011] Preferably, the shell has a thickness of 1 to 50 nm, a porosity of 25 to 99%, a residual carbon content of 20 to 70 wt%, and a specific surface area of ​​1 to 20 m 2 / g.

[0012] Preferably, the modified resin-coated sulfur-doped microcrystalline graphite negative electrode material is a spherical particle or a quasi-spherical particle with a specific surface area of ​​1 to 100 m 2 / g; 2t compaction density is 0.7~5.0g / cm 3 ; Tap density is 0.5~3.0g / cm 3 ; Porosity is 20-90%; Particle size D50 is 2-10μm.

[0013] As another object of the invention, the present invention also provides a method for preparing the above-mentioned modified resin-coated dual-doped microcrystalline graphite negative electrode material, comprising the following steps:

[0014] S1. Activation doping; activating the microcrystalline graphite with an activating agent and then drying it to form a porous structure, thereby obtaining activated microcrystalline graphite;

[0015] S2. Sulfur doping; after uniformly mixing the metal-doped microcrystalline graphite and the sulfur source, a sulfur doping reaction is performed to obtain a dual-doped microcrystalline graphite;

[0016] S3. Coating: coating the surface of the dual-doped microcrystalline graphite with a nitrogen-doped organic resin material, and then carbonizing the material to form a coating layer formed by coating the surface of the dual-doped microcrystalline graphite with a nitrogen-doped hard carbon material.

[0017] In some specific embodiments, in S1, the activation treatment includes uniformly mixing the microcrystalline graphite, the activator, water and the metal salt and then drying it for the first time; then heating it to 700-1100°C at a heating rate of 2-10°C / min and keeping it warm for 1-4 hours; while metal doping is being performed, pores are formed inside the microcrystalline graphite during the drying process to improve the sodium storage capacity of the material, and metal doping is used to form chemical bonds between sulfur and microcrystalline graphite to improve the material's cycle and rate capabilities.

[0018] Preferably, the ratio of the metal salt to the microcrystalline graphite is 0.05-0.2:1.

[0019] Preferably, the mass ratio of the activator to the microcrystalline graphite is 0.1-0.5:1.

[0020] Preferably, the activating agent is a base.

[0021] More preferably, the base is one or more of lithium hydroxide, sodium hydroxide and potassium hydroxide.

[0022] Preferably, the first drying includes any one of freeze drying, vacuum drying and forced air drying; most preferably, it is freeze drying.

[0023] In some specific embodiments, in S2, the sulfur doping reaction includes solid phase doping or liquid phase doping.

[0024] Preferably, the solid phase doping comprises uniformly mixing the metal-doped microcrystalline graphite and the sulfur source, and then heat-treating the mixture at 100 to 300° C. for 12 to 36 hours in a nitrogen atmosphere.

[0025] More preferably, the solid phase doping mixing method includes at least one of mechanical mixing, mechanical stirring, and ball milling.

[0026] Preferably, the liquid phase doping includes a solvothermal reaction; the temperature of the solvothermal reaction is 80 to 300° C. and the time is 2 to 6 hours.

[0027] Preferably, the mass ratio of the sulfur in the sulfur source to the carbon in the activated microcrystalline graphite is 1:3-6.

[0028] In some specific embodiments, in S3, the nitrogen-doped organic resin is prepared by mixing a nitrogen source with an organic resin material and then adding the mixture to an organic solvent, raising the temperature to 200-350° C. and keeping the temperature for 30-90 min; and finally performing a second drying.

[0029] Preferably, the second drying includes any one of vacuum drying, spray drying and air drying.

[0030] Preferably, the organic solvent is at least one of quinoline, tetrahydrofuran, toluene and benzene.

[0031] Preferably, the ratio of the volume of the organic solvent to the mass of the organic resin material is 100:1-10.

[0032] Preferably, the coating includes solid phase coating or liquid phase coating.

[0033] Preferably, the mass ratio of the nitrogen-doped organic resin material to the microcrystalline graphite is 1:8-13.

[0034] Preferably, the nitrogen source is a mixture of one or more of melamine, polypropylamine, polyvinyl pyrrolidone, ammonium chloride and dopamine.

[0035] More preferably, the mass ratio of the nitrogen source to the activated microcrystalline graphite is 1:0.05-0.3.

[0036] Preferably, the carbonization treatment is carried out in a protective atmosphere at a temperature of 800 to 1300° C. and for a time of 8 to 16 hours.

[0037] More preferably, the protective atmosphere comprises any one of an inert gas or nitrogen.

[0038] Preferably, the particle size D10 of the microcrystalline graphite is 1 to 15 μm; D50 is 5 to 40 μm; and D90 is 8 to 80 μm.

[0039] Preferably, the specific surface area of ​​the microcrystalline graphite is 10 to 300 m 2 / g; tap density is 0.4~2.0g / cm 3 .

[0040] As one of the aspects of the invention, the present invention also provides a sodium battery negative electrode, which at least includes the above-mentioned modified resin-coated dual-doped microcrystalline graphite negative electrode material.

[0041] As one aspect of the invention, the present invention also provides a sodium ion battery, comprising at least the above-mentioned sodium battery negative electrode.

[0042] Natural microcrystalline graphite has fine grains, dispersed orientation, and has the characteristics of near isotropy, which is conducive to the rapid migration of sodium ions. As a negative electrode material for sodium ion batteries, it has more active sites. However, due to the large radius of sodium ions, natural microcrystalline graphite cannot be directly used in sodium ion batteries, and it is difficult to freely embed and remove sodium ions, resulting in a low sodium storage capacity. Therefore, the present invention is activated by treating microcrystalline graphite, and the porous structure formed has a higher specific surface area, thereby increasing the number of active sites of natural microcrystalline graphite. At the same time, metal doping is carried out while activating the treatment, and metal ions also enter the holes more easily while forming a porous structure, and in the subsequent sulfur doping process, it is also more conducive to sulfur filling to the interlayer and porous structure of microcrystalline graphite, thereby increasing the active sites of microcrystalline graphite. In this step, the step and metal doping are carried out simultaneously. Taking potassium hydroxide as an example, potassium hydroxide generates potassium carbonate or potassium oxide reacts with carbon (microcrystalline graphite) to form a porous structure, and metal doping is carried out simultaneously. Then, through freeze-drying treatment, more pore structures are provided for the microcrystalline graphite, and the interlayer spacing of the microcrystalline graphite is further increased, which is more conducive to the deintercalation of sodium ions.

[0043] Furthermore, the metal-doped microcrystalline graphite is further sulfur-doped, and the obtained dual-doped microcrystalline graphite has more and different active sites, including defect sites, a large number of edge active sites and sulfur-doped active sites formed in the ordered-disordered chaotic layer stacking structure of the microcrystalline graphite, and the active sites can not only be located on the surface of the microcrystalline graphite, but also enter the interlayer structure of the microcrystalline graphite, thereby providing a basis for improving the sodium storage capacity; further, the present invention uses dual doping of metal and sulfur to form metal salts with sulfur and microcrystalline graphite on the surface of the microcrystalline graphite and inside the porous structure. Chemical bonds are formed, thereby providing a bridge for the bonding between microcrystalline graphite and sodium ions, thereby solving the problem of sodium ion loss during the cyclic charge and discharge process caused by the weak bonding between sodium ions and microcrystalline graphite; moreover, the surface of the dual-doped microcrystalline graphite is coated with nitrogen-doped hard carbon materials to give the surface a three-dimensional porous conductive network structure, the nitrogen-doped hard carbon material and the sulfur-doped microcrystalline graphite can be in full contact, and the mutual attraction of the lone pair of electrons of the nitrogen element to the polysulfides generated during the charge and discharge process can effectively inhibit the loss and shuttle effect of sodium ions, thereby improving the cycle stability of the battery.

[0044] Beneficial technical effects obtained by the present invention:

[0045] 1. The present invention increases the interlayer spacing and active sites of microcrystalline graphite through an activation process, and then performs dual doping of sulfur and metal salt to increase the doping amount of sulfur and metal salt in the microcrystalline graphite. At the same time, the metal salt forms a chemical bond between sulfur and microcrystalline graphite, which reduces the loss of sodium ions during the charge and discharge process, improves the material stability, and increases the rate cycle performance of the sodium ion battery.

[0046] 2. By using nitrogen-doped hard carbon materials to coat the dual-doped microcrystalline graphite, not only a three-dimensional conductive network structure is formed on the surface of the negative electrode material to promote electron transfer and improve the conductivity of the material, but also the nitrogen-doping and sulfur-doping with core-shell structures are fully contacted at the interface, which further inhibits the loss of sodium ions during the charge and discharge process, thereby improving the structural stability of the material, alleviating the volume effect generated during the charge and discharge process, and improving the cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is an electron microscope image of the modified resin-coated sulfur-doped microcrystalline graphite negative electrode material prepared in Example 1 of the present invention.

[0048] Figure 2 Schematic diagram of the capacity retention rate of the modified resin-coated sulfur-doped microcrystalline graphite negative electrode material after 500 cycles prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0049] In view of the defects of the prior art, the present invention proposes a sodium ion secondary battery positive electrode active material and provides a preparation method thereof. The specific technical scheme of the present invention is described in detail below through specific implementation methods. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. In order to describe concisely, it is impossible for this specification to describe in detail all the features of the actual implementation methods. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in this specification should be known to those skilled in the art of this application.

[0051] The technical solution of the present invention is described in detail below through specific implementation methods.

[0052] Example 1

[0053] This embodiment provides a method for preparing a modified resin-coated sulfur-doped microcrystalline graphite negative electrode material, which uses microcrystalline graphite as a base material, is doped with metal salt and sulfur, and then coated with a nitrogen-doped organic resin. The specific preparation steps include:

[0054] In the first step, the microcrystalline graphite is crushed and graded until the D50 particle size of the material is 14.875 μm; the carbon content is 80.194%, the tap density is 0.583 g / cc, and the specific surface area is 28.771 m 2 / g.

[0055] In the second step, the crushed and classified microcrystalline graphite is purified using a ratio of hydrofluoric acid: nitric acid: hydrochloric acid: microcrystalline graphite of 0.4:0.6:0.3:1, and the mixture is treated at 200 rpm for 12 hours, followed by washing with water until the pH value is about 5.0.

[0056] The third step is to activate and dope the purified microcrystalline graphite. The activator potassium hydroxide: water: nickel sulfate: microcrystalline graphite are mixed in a ratio of 0.1:5:0.05:1, stirred, and freeze-dried at -60°C for 12 hours. The dried sample is heated to 800°C at a rate of 5°C / min and kept warm for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0057] In the fourth step, the activated metal-doped microcrystalline graphite and sublimated sulfur are mixed in a mass ratio of 7:3 using a VC mixer for 30 minutes, and heat-treated at 155°C for 20 hours in a nitrogen atmosphere to obtain microcrystalline graphite doped with metal and sulfur, i.e., the coated precursor.

[0058] In the fifth step, phenolic resin, polypropylamine and tetrahydrofuran are mixed in a mass ratio of 1:0.1:5 and heated at 250° C. to mix evenly, and then dried at 120° C. in a vacuum dryer to obtain a nitrogen-doped modified resin.

[0059] The sixth step is to coat the microcrystalline graphite with the nitrogen-doped modified resin as a coating material. The specific steps include: mixing the coating precursor and the nitrogen-doped modified resin in liquid phase, wherein the mass ratio of the coating precursor, the nitrogen-doped modified resin and water is 1:12:40; after mixing evenly, spray drying at 150°C is performed, and heat preservation at 1150°C for 8 hours to complete the coating of the coating precursor and form a coating layer, thereby obtaining the modified resin-coated sulfur-doped microcrystalline graphite negative electrode material.

[0060] The thickness of the coating layer is 40 nm.

[0061] See also Figure 1 , is an electron microscope image of the modified resin-coated sulfur-doped microcrystalline graphite negative electrode material prepared in this embodiment. It can be seen from the figure that the doped microcrystalline graphite negative electrode material is spherical particles or quasi-spherical particles.

[0062] Example 2

[0063] The difference between this embodiment and embodiment 1 is that the addition ratio of nickel sulfate in the third step is different. Specifically, in the third step, the purified microcrystalline graphite is activated and doped, potassium hydroxide: water: nickel sulfate: microcrystalline graphite is mixed in a ratio of 0.1:5:0.2:1, stirred, and freeze-dried at -60°C for 12 hours, and the dried sample is heated to 800°C at a rate of 5°C / min and kept warm for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0064] The first step, the second step, and the fourth to sixth steps are the same as those in Example 1.

[0065] Example 3

[0066] The difference between this embodiment and embodiment 1 is that the addition ratio of the activator in the third step is different. Specifically, in the third step, the purified microcrystalline graphite is activated and doped, potassium hydroxide: water: nickel sulfate: microcrystalline graphite is mixed in a ratio of 0.5:5:0.05:1, stirred, and freeze-dried at -60°C for 12 hours, and the dried sample is heated to 800°C at a rate of 5°C / min and kept warm for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0067] The first step, the second step, and the fourth to sixth steps are the same as those in Example 1.

[0068] Example 4

[0069] The difference between this embodiment and embodiment 1 is that the drying method in the third step is different. The drying method adopted in this embodiment is vacuum drying.

[0070] In this embodiment, the purified microcrystalline graphite is activated and doped. The activator potassium hydroxide: water: nickel sulfate: microcrystalline graphite is mixed in a ratio of 0.1:5:0.05:1 and stirred. The mixture is then dried in a vacuum for 12 hours. The dried sample is heated to 800°C at a rate of 5°C / min and kept warm for 2 hours to obtain activated metal-doped microcrystalline graphite.

[0071] Example 5

[0072] The difference between this embodiment and embodiment 1 is that in the third step, different metal salts are used. The metal salt used in this embodiment is sodium carbonate, which specifically includes:

[0073] The third step is to activate and dope the purified microcrystalline graphite. The activator potassium hydroxide: water: sodium carbonate: microcrystalline graphite are mixed in a ratio of 0.1:5:0.05:1, stirred, and freeze-dried at -60°C for 12 hours. The dried sample is heated to 800°C at a rate of 5°C / min and kept warm for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0074] Example 6

[0075] The difference between this embodiment and embodiment 1 is that in the third step, the heating rate is different, specifically including:

[0076] The third step is to activate and dope the purified microcrystalline graphite. The activator potassium hydroxide: water: nickel sulfate: microcrystalline graphite are mixed in a ratio of 0.1:5:0.05:1, stirred, and freeze-dried at -60°C for 12 hours. The dried sample is heated to 800°C at a rate of 10°C / min and kept warm for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0077] Example 7

[0078] The difference between this embodiment and embodiment 1 is that in the third step, the heating rate is different, specifically including:

[0079] The third step is to activate and dope the purified microcrystalline graphite. The activator potassium hydroxide: water: nickel sulfate: microcrystalline graphite are mixed in a ratio of 0.1:5:0.05:1, stirred, and freeze-dried at -60°C for 12 hours. The dried sample is heated to 800°C at a rate of 2°C / min and kept warm for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0080] Example 8

[0081] The difference between this embodiment and embodiment 1 is that in the third step, the temperature of heating is different, which specifically includes:

[0082] The third step is to activate and dope the purified microcrystalline graphite. The activator potassium hydroxide: water: nickel sulfate: microcrystalline graphite are mixed in a ratio of 0.1:5:0.05:1 and stirred. The mixture is freeze-dried at -60°C for 12 hours. The dried sample is heated to 1100°C at a rate of 5°C / min and kept warm for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0083] Example 9

[0084] The difference between this embodiment and embodiment 1 is that in the third step, the heating rate is different, specifically including:

[0085] The third step is to activate and dope the purified microcrystalline graphite. The activator potassium hydroxide: water: nickel sulfate: microcrystalline graphite are mixed in a ratio of 0.1:5:0.05:1, stirred, and freeze-dried at -60°C for 12 hours. The dried sample is heated to 1100°C at a rate of 7°C / min and kept warm for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0086] Comparative Example 1

[0087] The only difference between this comparative example and Example 1 is that the third step of activation doping treatment is not included, that is, the microcrystalline graphite is neither activated nor metal doped, that is, the microcrystalline graphite after the second step of purification is directly sulfur-doped with sublimated sulfur.

[0088] The first step, the second step, and the fourth to sixth steps are the same as those in Example 1.

[0089] Comparative Example 2

[0090] The difference between this comparative example and Example 1 is that in the third step, no metal salt is added, and only an activation step is performed, specifically including:

[0091] The first and second steps are the same as in Example 1.

[0092] The third step is to activate the purified microcrystalline graphite by mixing activator potassium hydroxide: water: microcrystalline graphite in a ratio of 0.2:5:1 and stirring, and freeze-drying at -60°C for 12 hours. The dried sample is heated to 800°C at a rate of 5°C / min and kept warm for 2 hours to obtain activated microcrystalline graphite.

[0093] In the fourth step, the activated microcrystalline graphite and the sublimated sulfur are mixed in a mass ratio of 7:3 using a VC mixer for 30 minutes, and heat-treated at 155° C. for 20 hours in a nitrogen atmosphere to obtain sulfur-doped microcrystalline graphite, i.e., a coated precursor.

[0094] The fifth and sixth steps are the same as those in Example 1.

[0095] Comparative Example 3

[0096] The difference between this comparative example and Example 1 is that in the third step, no activator is added and only metal doping is performed.

[0097] Specifically include:

[0098] The first and second steps are the same as in Example 1.

[0099] The third step is to activate the purified microcrystalline graphite. Water: nickel sulfate: microcrystalline graphite are mixed in a ratio of 5:0.05:1 and stirred. The mixture is freeze-dried at -60°C for 12 hours. The dried sample is heated to 800°C at a rate of 5°C / min and kept warm for 2 hours to obtain activated microcrystalline graphite.

[0100] In the fourth step, the activated microcrystalline graphite and the sublimated sulfur are mixed in a mass ratio of 7:3 using a VC mixer for 30 minutes, and heat-treated at 155° C. for 20 hours in a nitrogen atmosphere to obtain sulfur-doped microcrystalline graphite, i.e., a coated precursor.

[0101] The fifth and sixth steps are the same as those in Example 1.

[0102] Comparative Example 4

[0103] The difference between this comparative example and Example 1 is that in the third step of the activation doping treatment, a conventional drying method is used for drying, specifically:

[0104] The third step is to activate and dope the purified microcrystalline graphite. The activator potassium hydroxide: water: nickel sulfate: microcrystalline graphite are mixed in a ratio of 0.2:5:0.05:1 and stirred. The mixture is then dried at 100°C in an oven at normal pressure for 12 hours. The dried sample is heated to 800°C at a rate of 5°C / min and kept at this temperature for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0105] The other steps are the same as those in Example 1.

[0106] Comparative Example 5

[0107] The difference between this comparative example and Example 1 is that the fourth step is not included, that is, sulfur doping is not performed, and the obtained microcrystalline graphite is activated metal-doped microcrystalline graphite, which is then directly nitrogen-doped and coated. Specifically, it includes:

[0108] The first to third steps are the same as those in the example, and then the activated metal-doped microcrystalline graphite obtained is directly used as a coating precursor; the subsequent steps are the same as the fifth and sixth steps of Example 1.

[0109] Comparative Example 6

[0110] The only difference between this comparative example and Example 1 is that it does not include the step of coating the coating precursor, but only includes the first to fourth steps in Example 1, and the obtained coating precursor, i.e., metal and sulfur dual-doped microcrystalline graphite, is used as the negative electrode material.

[0111] Comparative Example 7

[0112] The difference between this comparative example and Example 1 is that in the third step, the temperature of heating is different, specifically including:

[0113] The third step is to activate and dope the purified microcrystalline graphite. The activator potassium hydroxide: water: nickel sulfate: microcrystalline graphite are mixed in a ratio of 0.1:5:0.05:1, stirred, and freeze-dried at -60°C for 12 hours. The dried sample is heated to 1100°C at a rate of 12°C / min and kept warm for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0114] Comparative Example 8

[0115] The difference between this comparative example and Example 1 is that in the third step, the temperature of heating is different, specifically including:

[0116] The third step is to activate and dope the purified microcrystalline graphite. The activator potassium hydroxide: water: nickel sulfate: microcrystalline graphite are mixed in a ratio of 0.1:5:0.05:1, stirred, and freeze-dried at -60°C for 12 hours. The dried sample is heated to 600°C at a rate of 5°C / min and kept warm for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0117] Comparative Example 9

[0118] The difference between this comparative example and Example 1 is that in the third step, the temperature of heating is different, specifically including:

[0119] The third step is to activate and dope the purified microcrystalline graphite. The activator potassium hydroxide: water: nickel sulfate: microcrystalline graphite are mixed in a ratio of 0.1:5:0.05:1, stirred, and freeze-dried at -60°C for 12 hours. The dried sample is heated to 1200°C at a rate of 5°C / min and kept warm for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0120] Comparative Example 10

[0121] The difference between this comparative example and Example 1 is that in the third step, the temperature of heating is different, specifically including:

[0122] The third step is to activate and dope the purified microcrystalline graphite. The activator potassium hydroxide: water: nickel sulfate: microcrystalline graphite are mixed in a ratio of 0.1:5:0.05:1, stirred, and freeze-dried at -60°C for 12 hours. The dried sample is heated to 600°C at a rate of 5°C / min and kept warm for 2 hours to obtain the activated metal-doped microcrystalline graphite.

[0123] Full battery preparation and testing: The prepared microcrystalline graphite negative electrode material, carboxymethyl cellulose and styrene butadiene rubber were dissolved in deionized water at a mass ratio of 96.5:1.5:1, the solid content was controlled to be 50%, and the negative electrode was coated on a copper foil current collector and vacuum dried to obtain a negative electrode. Lithium cobalt oxide, polyvinylidene fluoride and conductive carbon were dissolved in N-methylpyrrolidone at a mass ratio of 97:2:1, the solid content was controlled to be 50%, and the positive electrode was coated on an aluminum foil current collector and vacuum dried to obtain a positive electrode. The battery assembly and testing were completed in the room. After activation, the battery was charged and discharged at a high temperature of 45°C with a charge and discharge range of 3V to 4.4V. The specific charge and discharge conditions were that the battery was kept at a constant temperature of 45°C for 1h, then charged at a constant current of 4C for 9min, charged at a constant current of 2.5C for 4.8min, charged at a constant current of 1.5C to 4.4V, the cut-off current was 0.05C, left for 5min, discharged at a constant current of 1C, the cut-off voltage was 3V, left for 5min, and the cycle was repeated for 600 weeks, and the capacity retention rate R was recorded. The test results of physical properties and electrochemical properties are shown in Table 1.

[0124] See also Figure 2 , is a schematic diagram of the capacity retention rate of the negative electrode material prepared in Example 1 after 500 cycles.

[0125] Table 1 Physical properties and electrochemical performance test results of examples and comparative examples

[0126]

[0127] From the results in Table 1, it can be seen that the present invention uses metal salt and sulfur doped microcrystalline graphite and adds modified resin to form a core-shell structure, which can significantly improve the cycle stability of the negative electrode material. Specifically, Example 1 is compared with Example 6-Example 9, and Comparative Example 7-Comparative Example 9. When the heating rate is 2-5°C / min, the molten potassium hydroxide is better in contact with the microcrystalline graphite, showing a similar activation effect, and the physical properties and electrochemical properties of the negative electrode material are similar. When the heating rate continues to increase, the effect decreases, and after exceeding 10°C / min, the performance of the obtained negative electrode material can no longer meet the requirements; and when the activation temperature is lower than 700°C or higher than 1100°C, the cycle performance of the negative electrode material is significantly reduced when the activation temperature is kept at this activation temperature.

[0128] The above are only preferred embodiments of the present invention, which do not limit the protection scope of the present invention. For those skilled in the art, the present invention may have various modifications and changes. Within the spirit and principle of the present invention, changes, modifications, replacements, integrations and parameter changes to these embodiments by conventional substitutions or capable of achieving the same functions without departing from the principles and spirit of the present invention all fall within the protection scope of the present invention.

Claims

1. A modified resin-coated dual-doped microcrystalline graphite negative electrode material having a core-shell structure, including a core and an outer shell; The core is double-doped microcrystalline graphite and has a three-dimensional network porous structure; The dual-doped microcrystalline graphite includes metal doping and sulfur doping; The shell is a coating layer formed by carbonizing the modified resin and coated on the surface of the core; the shell has a three-dimensional porous conductive network structure.

2. The modified resin-coated dual-doped microcrystalline graphite negative electrode material according to claim 1, characterized in that: In the shell, the modified resin is a nitrogen-doped organic resin material; the organic resin material includes one or more combinations of epoxy resin, phenolic resin, petroleum resin, urea-formaldehyde resin, and furan resin; The nitrogen source in the nitrogen doping is a combination of one or more of melamine, polypropylamine, polyvinyl pyrrolidone, ammonium chloride and dopamine; And / or, in the core, the metal doping is metal salt doped in a microcrystalline graphite matrix material; The metal salt is a combination of one or more of nickel sulfate, sodium carbonate, manganese sulfate, cobalt nitrate, and ferric chloride; In the sulfur doping, the sulfur source is at least one of sublimated sulfur, sodium thiosulfate, and carbon disulfide.

3. The modified resin-coated dual-doped microcrystalline graphite negative electrode material according to claim 1, characterized in that: The shell has a thickness of 1-50 nm, a porosity of 25-99%, a carbon residue of 20-70 wt%, and a specific surface area of ​​1-20 m 2 / g; The modified resin-coated sulfur-doped microcrystalline graphite negative electrode material is a spherical particle or a quasi-spherical particle with a specific surface area of ​​1 to 100 m 2 / g; 2t compaction density is 0.7~5.0g / cm 3 ; Tap density is 0.5~3.0g / cm 3 ; Porosity 20~90%; Particle size D 50 2~10μm.

4. A method for preparing a modified resin-coated dual-doped microcrystalline graphite negative electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Activation doping treatment; after mixing the microcrystalline graphite, the activator and the metal salt, drying is performed for the first time; and then heating-insulating treatment is performed to obtain metal-doped microcrystalline graphite having a three-dimensional porous network structure; S2. sulfur doping; mixing the metal-doped microcrystalline graphite with a sulfur source and performing a sulfur doping reaction to obtain a dual-doped microcrystalline graphite; S3. Coating: coating the surface of the dual-doped microcrystalline graphite with a nitrogen-doped organic resin material, and then carbonizing the material to form a coating layer formed by coating the surface of the dual-doped microcrystalline graphite with a nitrogen-doped hard carbon material.

5. The preparation method according to claim 4, characterized in that: In S1, the drying includes any one of freeze drying, vacuum drying, and forced air drying; preferably freeze drying; The freeze-drying conditions include freeze-drying at -60°C for 12h; The heating-keeping treatment includes heating to 700-1100° C. at a heating rate of 2-10° C. / min and then keeping the temperature for 1-4 hours; And / or, the mass ratio of the activator to the microcrystalline graphite is 0.1-0.5:1; The activator is a base; preferably, the base is one or more of lithium hydroxide, sodium hydroxide, and potassium hydroxide; And / or, the metal salt may be a combination of one or more of nickel sulfate, sodium carbonate, manganese sulfate, cobalt nitrate, and ferric chloride; The ratio of the metal salt to the microcrystalline graphite is 0.05-0.2:

1.

6. The preparation method according to claim 4, characterized in that: In S2, the sulfur doping includes solid phase doping or liquid phase doping; The solid phase doping includes at least one of mechanical mixing, mechanical stirring, and ball milling; Or, the liquid phase doping includes a solvothermal reaction; the solvothermal reaction temperature is 80 to 300° C., and the time is 2 to 6 hours; And / or, the mass ratio of the sulfur source to the activated microcrystalline graphite is 1:3-6.

7. The preparation method according to claim 4, characterized in that: In S3, the preparation of the nitrogen-doped organic resin includes mixing a nitrogen source with an organic resin material and adding the mixture to an organic solvent, raising the temperature to 200-350° C., and maintaining the temperature for 30-90 minutes; and finally drying the mixture; the drying includes any one of vacuum drying, spray drying, and forced air drying; The organic solvent is at least one of quinoline, tetrahydrofuran, toluene and benzene, or a combination of two or more thereof; The volume ratio of the organic solvent to the mass ratio of the organic resin material is 100:1-10; The coating includes solid phase coating or liquid phase coating; The mass ratio of the nitrogen-doped organic resin material to the microcrystalline graphite is 1:8-13; The carbonization treatment is carried out in a protective atmosphere at a temperature of 800-1300° C. for 8-16 hours; preferably, the protective atmosphere includes any one of an inert gas or nitrogen.

8. The preparation method according to any one of claims 4 to 7, characterized in that: D50 is 5~40μm; The specific surface area of ​​microcrystalline graphite is 10~300 m 2 / g; tap density is 0.4 ~2.0g / cm 3 .

9. A sodium battery negative electrode, comprising at least the modified resin-coated dual-doped microcrystalline graphite negative electrode material according to any one of claims 1 to 3.

10. A sodium ion battery, comprising at least the sodium battery negative electrode according to claim 9.

Citation Information

Patent Citations

  • Preparation method of microcrystalline graphite-hard carbon composite negative electrode material

    CN107437613A

  • Hard carbon coated expanded microcrystalline graphite material as well as preparation method and application thereof in sodium ion battery

    CN109616639A

Cited By

  • Spherical graphite negative electrode material with controllable morphology and preparation method thereof

    CN120767301A

  • Shape-controllable spherical graphite negative electrode material and preparation method thereof

    CN120767301B

  • Recycling method of lithium iron phosphate positive electrode material and lithium iron phosphate positive electrode material

    CN121237826A

  • Carbon material and preparation method and application thereof

    CN122301208A